Training in Islamic Rituals: A Solution to Muslim Extremism - Ramzy, Mohammad Ismath (KATHA- The Official Journal of the Centre for Civilisational Dialogue, 2011)
The rise of radical movements and its rhetorical advocacy to reconstruct Muslim society raised the question on the connection between religion and extremism. The majority of policy makers and social scientists seem to be convinced that increasing religious awareness among the Muslims have led to violence against others. Hence, the war against terrorism targets religious awareness among the Muslims and use strategies to secularize Muslim societies. However, secularization in the Muslim world has increased violence instead of decreasing it. This article puts forward that religious awareness and Islamic practices such as fasting during the month of Ramadhan can increase peace and harmony instead of violence. The recent statistics on religion and extremism also authenticate the positive aspect of religiosity and harmonious living.